Quantitative parameters of bacterial RNA polymerase open-complex formation, stabilization and disruption on a consensus promoter - Bera Subhas C; America Pim PB; Maatsola Santeri; Seifert Mona; Ostrofet Eugeniu; Cnossen Jelmer; Spermann Monika; Papini Flávia S; Depken Martin; Malinen Anssi M; Dulin David (Oxford University Press, 2025)
Transcription initiation is the first step in gene expression, and is therefore strongly regulated in all domains of life. The RNA polymerase (RNAP) first associates with the initiation factor σ to form a holoenzyme, which binds, bends and opens the promoter in a succession of reversible states. These states are critical for transcription regulation, but remain poorly understood. Here, we addressed the mechanism of open complex formation by monitoring its assembly/disassembly kinetics on individual consensus lacUV5 promoters using high-throughput single-molecule magnetic tweezers. We probed the key protein-DNA interactions governing the open-complex formation and dissociation pathway by modulating the dynamics at different concentrations of monovalent salts and varying temperatures. Consistent with ensemble studies, we observed that RNAP-promoter open (RPO) complex is a stable, slowly reversible state that is preceded by a kinetically significant open intermediate (RPI), from which the holoenzyme dissociates. A strong anion concentration and type dependence indicates that the RPO stabilization may involve sequence-independent interactions between the DNA and the holoenzyme, driven by a non-Coulombic effect consistent with the non-template DNA strand interacting with σ and the RNAP β subunit. The temperature dependence provides the energy scale of open-complex formation and further supports the existence of additional intermediates.